Potensi Penyerapan Karbon Pada Tegakan Damar Mata Kucing (Shorea Javanica) Di Pekon Gunung Kemala Krui Lampung Barat - Anna Herliyanti Maoelana Putri; Christine Wulandari (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Based on evolving issues and given the importance of the role of forests in a bsorbing carbon from the air and forest biomass, need a lot of research that could encourage the further development of carbon in biomass. The purpose of this study was to determine the potential for carbon stored in standing damar mata kucing (Shorea javanica). The experiment was conducted at Pekon Gunung Kemala Krui West Lampung, from May to Juni 2013. Methods used are non-destructive method. This method is away of sampling to perform measurements with out harvesting. Estimation oft he potential of carbon up take in stands with diameter >30cm using equations that have been validated. Estimate the relationship and influence of biomass and carbon is to make regression test. The results showed that the total biomass of 249,72 tons/ha and carbon sequestration in stands of damar mata kucing and 124,86 tons/ha. Based on the results of statistical tests in order to get the linear regression equation of the potential for carbon sequestration in Pekon Mount Kemala, namely Y(biomass) = -518,59 + 15,31 (density) + 9,02 (height)(R2 = 0,970) and Y(carbon)= -259,43 + 7,67 (density) + 4,51 (height) (R2 = 0,97). Keywords: damar mata kucing, carbon sequestration, non-destructive method, SPSS